MONEY SUPPLY IN INDONESIA 1990-2020: PARTIAL ADJUSTMENT MODEL APPLICATION - Lucida Ary Meidiani (Publikasi Indonesia, 2023)
The money supply is one of the important factors to maintain the stability of a country's economy. Factors that can affect the money supply include GDP, investment, and interest rates. The purpose of this research was to estimate the effect of GDP, investment, and interest rates on money supply growth in Indonesia from 1990-2020 both in the short and long-term using the Partial Adjustment Model (PAM) regression analysis. The regression results showed that GDP and investment had no effect on the money supply growth in Indonesia from 1990-2020, while interest rates had a negative effect. The government is expected to increase GDP and investment to boost consumption, so that people are prosperous and Indonesia's economic growth increases. This will lead to the increase in the money supply growth. In addition to the government, Bank Indonesia as the central bank is expected to be able to control interest rates so that they are not too high or too low, with the hope of maintaining the stability of the money supply so that the possibility of inflation causing economic downturn tends to be low